Empowering youth as vaccine advocates: Harnessing the power of educational videos - Ida, Rachmah; Kinasih, Sri Endah; Febriyanti, Syafrida Nurrahmi; Puspa, Ratih; Romadhona, Mochamad Kevin; Kim, Seokkyu (Universitas Islam Malang, 2024)
This community service program aims to empowering youth to build awareness to the comunity. This community service using service learning methods. The Various efforts have been made by the Government and society to deal with the COVID-19 pandemic, starting from maintaining distance, using masks, and washing hands to vaccination programs. Even so, public acceptance of COVID-19 vaccination is not always positive. There are still people who refuse to be vaccinated for various reasons, such as doubts about the effectiveness of vaccines, distrust of vaccines, concerns about side effects, and even religious reasons or the halalness of vaccines. This form of public resistance to vaccines does not only circulate in whispers between residents and other private spheres but also circulates through social media and WhatsApp groups. This community service is carried out by providing training in making educational videos to young people in Benowo District, Surabaya. the selection of teenage participants the main consideration is that teenagers are the most active social media users so with the training in making educational videos, it is hoped that teenagers can become peer educators who provide positive messages to their peers and older or younger people using -creative and innovative ways.